Molecular Mechanism of Tumor Cell Immune Escape Mediated by CD24/Siglec-10 - Yin, Shan-Shan; Gao, Feng-Hou (Frontiers in Immunology, 2020)
Tumor immune escape is an important part of tumor occurrence and development. Tumor cells can develop a variety of immunosuppressive mechanisms to combat tumor immunity. Exploring tumor cells that escape immune surveillance through the molecular mechanism of related immunosuppression in-depth is helpful to develop the treatment strategies of targeted tumor immune escape. The latest studies show that the CD24 on the surface of tumor cells interacts with the Siglec-10 on the surface of immune cells to promote the immune escape of tumor cells. This paper clarifies a treatment strategy that initiates the molecular mechanism of inhibiting the activation of immune cells and targeting CD24 on the surface of tumor cells or Siglec-10 on immune cells through the interaction between CD24 on tumor cells and Siglec-10 on immune cells.